Female Gender Is an Age-dependent Negative Prognostic Factor for Patients with Upper Tract Urothelial Carcinoma - Sikic, Danijel; Wach, Sven; Taubert, Helge; Richterstetter, Mario; Kunath, Frank; Goebell, Peter; Schick, Stefan; Olbert, Peter; Huber, Johannes; Wullich, Bernd; Keck, Bastian (Anticancer Research, 2015)
To analyze female gender as a possible age-dependent prognostic factor for overall (OS) and cancer-specific survival (CSS) in patients with upper urinary tract urothelial carcinoma (UUTUC) after radical nephroureterectomy (RNU).A total of 167 men and 101 women with UUTUC treated with RNU with bladder cuff resection at our clinic were retrospectively analyzed. Female patients were divided into pre- and post-menopausal groups and compared against male patients of the same age. We used a cut-off age of 59 years or more as a surrogate for the post-menopausal hormonal status of women. Kaplan-Meier analyses and multivariate Cox proportional hazards regression analyses were performed to analyze gender as a possible prognostic factor of OS and CSS.Women aged 59 years or more had a significantly worse CSS with an average of 231 months after RNU compared to 303 months for their male counterparts (p=0.011). Univariate Cox regression analysis showed a 2.44-fold higher risk of death (p=0.013), while multivariate analyses, adjusted for tumor stage and tumor grade, showed a 2.92-fold higher risk (p=0.011) of cancer-specific death for women aged 59 years or more.Female gender is an age-dependent prognostic factor for CSS for patients with UUTUC treated with RNU.
EVALuna2:16326